Stakeholders' Perceptions of Home-based Palliative Care for Cancer Patients During the COVID-19 Pandemic: A Qualitative Study - Suzanne Hojjat-Assari; Pooneh Pirjani; Vahid Kaveh; Heshmatolah Heydari; Ghazal Razani; Kosar Hossinie; Romina Sadeqian (Iran University of Medical Sciences, 2023)
Background: During the COVID-19 pandemic, care for cancer patients may be disrupted for several reasons, leading to disease progression. Home-Based palliative care, if properly managed, can provide easy and safe access to care services for these patients. This study aimed to explore stakeholders' perceptions of home-based palliative care for cancer patients during the pandemic. Methods: This qualitative study was conducted using conventional content analysis in Tehran, Iran, in 2021. By purposeful sampling, 19 participants, including cancer patients receiving home-based care services from the Iranian Cancer Control Center (MACSA) and their families, as well as the homecare providers, were recruited. The study data were generated by conducting 19 semi-structured interviews and a focus group session and analyzed based on the method proposed by Lundman and Graneheim. Results: Qualitative analysis of the data revealed 5 main categories: "need for remote services", "disease transmission reduction", "management requirements", "burnout", and "reducing hospital workload."  Conclusion: The use of telemedicine, the existence of call centers, and the designing of appropriate guidelines, along with the help of qualified personnel, prevent the transmission of COVID-19 to cancer patients in-home palliative care and lead to the provision of comprehensive care to these patients. This approach to care helps avert staff burnout and reduces the number of occupied beds in hospitals.